Autopercepción de la enfermedad periodontal en estudiantes de odontología de la universidad Antonio Nariño, Bucaramanga. (2024)
Periodontal disease is a multifactorial pathology that stands out for the infection of the tissues that help support the teeth and that arises mainly as a consequence of poor oral hygiene habits that generate dental plaque due to bacterial accumulation and can sometimes go unnoticed.